Comparing ’religious diversities’: Issues, perspectives and problems - Obadia, Lionel (Approaching Religion, 2017)
This paper aims at reopening the debate regarding ‘religious diversity’ in religious studies. A review of (recent or ancient) literature demonstrates that we have not finished with the complexity of the issue of ‘diversity’, whether in academic or social debates. Furthermore, diversity must not only be taken seriously, but impels us towards a comparative methodology in order to highlight the variations of the forms, dynamics, effects and contexts of diversity. As such, Asian countries represent a very interesting location for an epistemological deconstruction of the Western-style and monotheistic-centred concept of ‘religious diversity’, as it is often used in religious studies and the social sciences.